Enhancing competitiveness of small scale poultry egg production farm in the Democratic Republic of Congo - Tshibambe Ndjibu, Zephyrin (Kansas State University, 2015)
The rapidly changing economic environment in the Democratic Republic of Congo (DR Congo) offers significant opportunities for businesses. The food and agribusiness sector is one of the major opportunities for growth given that increasing incomes are going to enhance the food and nutrition security needs of an increasing segment of the population. Animal protein in the form of chicken meat and eggs are relatively inexpensive and offer an opportunity for entry and differentiation in a markets located in DR Congo’s largest cities of Kinshasa and Kananga. This thesis uses the case of Z-CO Farm in DR Congo to explore the strategic opportunities for small-scale egg production in a low-income but growing country. Having been in operation for a number of years, Z-CO Farms has been producing chicken eggs for the general consumer market. This thesis explores the opportunity to differentiate the market that Z-CO Farms targets with the view to enhance its competitiveness, expand the market boundaries and create new value for customers that produce significant rewards. The off-take for the project is the creation of Blue Ocean markets for chicken eggs in a market that is increasingly exposed to food safety risks by assuring consumers a safe product. This project, when implemented, would be the first in DR Congo. However, would it be profitable? Under what conditions would it be profitable? We employ three primary methods to answer the foregoing questions. First, we evaluate the literature and the available secondary data. Second, we use an economic and financial model to develop the foundation for conducting the analyses for assessing the feasibility of building a small-scale table egg production system to address the emerging higher income consumers in DR Congo. We draw on the blue ocean strategy eloquently presented by Kim and Mauborgne for insight and guidance in building a unique product and service offering for the identified markets in Kinshasa and Kananga. We assess four strategies: the base scenario of the current market conditions where Z-CO maintains its commodity red ocean engagement in the market; innovating its feeding program for the birds; pursuing a market segmentation program whereby it offers high value food safety value proposition to the middle and upper-middle class of consumers; and a combination of a feed innovation and market segmentation initiative. The results show that while the first two strategies returned a positive net present value (NPV) in Kananga, they failed in Kinshasa. This is because of the level of competition in Kinshasa compared to Kananga as well as the cost of operations in the two locations. The results also show that while the remaining two strategies were profitable in both markets, they offered higher NPV and internal rates of return in Kananga than in Kinshasa. The best outcome in operating in both cities involved the fourth strategy, producing a combined NPV of about $493,867. The principal driver for this superior performance in Kananga is cost of feed. There is, therefore, value in thinking about how to leverage this cost advantage in Kananga to enhance the profitability in Kinshasa because of the population and income advantage in the latter. The study provides insights for the management of Z-CO to pursue their future investment planning and in selecting the locations and size of their operations to maximize their NPV and IRR. It also identifies the principal sources of risks that Z-CO’s management must avoid or effectively manage to achieve their desired business outcomes.
Keywords: Poultry production; Democratic Republic of Congo; Blue ocean strategy; DR Congo; Egg production; Chickens; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Commerce-Business (0505)